Synthesis of bis-allyloxy functionalized polystyrene and poly (methyl methacrylate) macromonomers using a new ATRP initiator - Sane, Prakash S.; Palaskar, Dnyaneshwar V.; Wadgaonkar, Prakash P. (European Polymer Journal, 2011)
A new bis-allyloxy functionalized ATRP initiator, viz, 4,4-bis (4-(allyloxy) phenyl) penty1-2-bromo-2-methylpropanoate was synthesized starting from commercially available 4,4-bis (4-hydroxyphenyl) pentanoic acid. Atom transfer radical polymerization of styrene in bulk and that of methyl methacrylate in anisole using CuBr/N,N,N',N',N `'-pentamethyldiethyl-enetriamine system was carried out. The kinetic study of styrene polymerization showed controlled polymerization behavior. Bis-allyloxy functionalized well-defined polystyrene (M(n)(GPC): 13,600-28,250, PDI: 1.07-1.09) and poly (methyl methacrylate) (M(n)(GPC): 10,100-18,450, PDI: 1.23-1.34) macromonomers were obtained. The presence of allyloxy functionality was confirmed by (1)H NMR spectroscopy. The reactivity of allyloxy functionality was demonstrated by carrying out organic reactions such as addition of bromine and hydrosilylation on polystyrene macromonomer. Polystyrene macromonomer with bis-allyloxy functionality was transformed into bis-epoxy functionalized polystyrene macromonomer using 3-chloroperoxybenzoic acid. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Allyloxy end-functional polymer; Atom transfer radical polymerization (ATRP); Macromonomers; Poly (methyl methacrylate); Polystyrene